Perspectives on Mental Illness Stigma Among African Immigrant Pregnant and Post-Partum Women in an Urban Setting: A Brief Report (Mary Ann Liebert, 2022)
Purpose: This study assessed the perspectives of pregnant and postpartum African immigrant women on mental illness. Methods: We conducted a focus group session (n=14) among pregnant and postpartum African immigrant women in June 2020. We used an inductive driven thematic analysis to identify themes related to mental health stigma. Results: Five core themes emerged: conceptualization of mental health, community stigmatizing attitudes, biopsychosocial stressors, management of mental health, and methods to reduce stigma. Conclusion: Understanding the perspectives of pregnant African immigrant women at the intersection of their race, ethnicity, gender, and migration are necessary to improve engagement with mental health services.